2013
DOI: 10.1007/s12350-012-9664-0
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter evaluation of the appropriate use of single-photon emission tomography myocardial perfusion imaging in Greece

Abstract: The appropriate use of MPI is relatively high, but a considerable proportion of inappropriate scans is noted which is associated with markers of lower risk. The most common source of inappropriate testing is the assessment of asymptomatic patients <2 years after PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…As shown in Table 2, these categorizations for PET appropriate use are similar to those found in the majority of reports with SPECT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although there are some reports of SPECT MPI with higher frequency of inappropriate studies. 19,27 For evaluation of the scintigraphic findings and outcomes, the authors have combined ''appropriate'' with ''uncertain'' categories, which although somewhat controversial, is consistent with the intent of these AUC-''uncertain is assumed to not provide grounds for denial of reimbursement.''…”
supporting
confidence: 72%
“…As shown in Table 2, these categorizations for PET appropriate use are similar to those found in the majority of reports with SPECT, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] although there are some reports of SPECT MPI with higher frequency of inappropriate studies. 19,27 For evaluation of the scintigraphic findings and outcomes, the authors have combined ''appropriate'' with ''uncertain'' categories, which although somewhat controversial, is consistent with the intent of these AUC-''uncertain is assumed to not provide grounds for denial of reimbursement.''…”
supporting
confidence: 72%
“…The 2005 AUC were used by 6 studies, 16,18,19,39,42,44 and the remainder used the 2009 AUC. 1015,17,20,3438,40,41,43 Single-photon emission computed tomography (SPECT) was the modality utilized in most of the studies, 1320,3436,38,39,4144 one study reported using positron emission tomography (PET), 12 while the remainder of the studies did not specify. 10,11,37,40 Among the included studies, 5 were conducted outside the United States.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,37,40 Among the included studies, 5 were conducted outside the United States. 11,17,34,38,41 Patients were recruited from the outpatient setting in 3 studies, 20,35,37 from an inpatient setting in 1 study, 10 and from both settings in 13 studies. 11–16,19,34,36,38,40,42,43 Overall, the summary rate for inappropriate testing was 14.8% (95% CI 11.6–18.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Previous retrospective studies using the AUC to classify imaging have identified rates of up to 22 % for TTE in the category of rarely appropriate, from a variety of clinical settings [ 7 10 ]. Appropriateness studies of single-photon emission tomography myocardial perfusion imaging (SPECT), and cardiac catheterization have shown similar rates of rarely appropriate use [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%